2003
DOI: 10.1161/01.str.0000051729.79990.fb
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection for Carotid Endarterectomy

Abstract: Background and Purpose-Risk-factor modeling has been proposed to identify patients with carotid stenosis who will most benefit from surgery. Validation by independent institutions performing carotid endarterectomy is necessary to determine the applicability of such models to the individual patient. Methods-A series of patients with a recently symptomatic high-grade carotid stenosis were selected for surgery according to current guidelines and were consecutively operated on in a single institution. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Although external validation is an essential step in prediction model development, only 4 of the 30 included models had been externally validated in an independent patient population before; 2 were externally validated in the same article in which their development was described (Alcocer 2013 and Cheng 2016), 16 , 17 and the other 2 had each been validated twice in independent validation studies (Rothwell 1999 and Tu 2003). 18 21 Our findings are similar to the findings of these previous studies, except that the discriminative performance of the Tu 2003 and Cheng 2016 models was slightly better in the previous external validations. A calibration plot was reported for only one of the previous external validation studies, 19 whereas we reported calibration plots for each prediction model that we validated.…”
Section: Discussionsupporting
confidence: 90%
“…Although external validation is an essential step in prediction model development, only 4 of the 30 included models had been externally validated in an independent patient population before; 2 were externally validated in the same article in which their development was described (Alcocer 2013 and Cheng 2016), 16 , 17 and the other 2 had each been validated twice in independent validation studies (Rothwell 1999 and Tu 2003). 18 21 Our findings are similar to the findings of these previous studies, except that the discriminative performance of the Tu 2003 and Cheng 2016 models was slightly better in the previous external validations. A calibration plot was reported for only one of the previous external validation studies, 19 whereas we reported calibration plots for each prediction model that we validated.…”
Section: Discussionsupporting
confidence: 90%
“…Out of the 12 externally validated models, nine (75%) were solely externally validated in the same paper in which their development was described, and three (25%) were validated by independent researchers. 8 10 …”
Section: Resultsmentioning
confidence: 99%